An Objective and Subjective Study of Noise Exposure within the Frequency Range from 10 kHz to 40 kHz - SMAGOWSKA, Bożena (Archives of Acoustics, 2013)
The paper consists of study results of exposure to high frequency noise at metalworking workplaces.The study was carried out using objective methods (measurements of parameters characterizing the noise)and subjective studies (questionnaire survey). Metalworking workplaces were located in a steel structure(e.g. deck gratings) of the manufacturing plant. The results are equivalent sound pressure levels in the1/3 octave frequency bands with center frequencies from 10 kHz to 40 kHz in reference to an 8-hourworkday equal to approximately 81–105 dB at most of the tested workplaces and exceed permissiblevalues. The questionnaire survey of annoyance high frequency noise (i.e. in the audible frequency and lowultrasound range) was conducted among 52 operators of machines. Most of the workers describe the noiseas: buzzing, insistent, whistling and high-pitched squeaky. Respondents specify the noise levels occurringat workplaces as: loud, impeding communication, highly strenuous and tiring.